The Effect of Game-Like Exercises on the Development of Strength Endurance and its Relationship with Shooting among Beach Soccer Players - Hussein, Raad (Journal of Physical Education, 2016)
As one of the team sports with changing motor performance, beach soccer needs special physical qualities due to the (small playing court, short time match, sandy ground, and the few number of players). Players should have a high level of these qualities as well as some basic skills needed in tactical performance in matches. Hence is the importance of the study in using game-like exercises to develop strength endurance and finding out its relationship with shooting in beach soccer. The researcher as a beach soccer player in the Iraqi national team has diagnosed the weaknesses of the Iraqi players throughout beach soccer tournament and suggested to develop some special physical abilities; strength endurance comes in forefront. The experimental method has been selected according to one group design with pre and posttests. The population of the study has been purposively chosen from the national team of beach soccer totaling (12) players. Two players were excluded and (10) players purposively selected to be the subject of the study rating 83.3% of the population; all submitted to the game –like exercises. Conclusions have showed that both of strength endurance and shooting skill have been developed among beach soccer players. The researcher accordingly has recommended conducting more research and studies using game-like exercises on soccer and futsal.